RAPD Analysis TO Assess the Genetic Stability in Tissue Culture Derived Black Pepper Plants - Haneesh Babu T P (Department Of Plantation Crops And Spices,College Of Horticulture, 2000)
As part of the Post Graduate programme in the Department of Plantation Crops and Spices, College of Horticulture, Vellanikkara experiments were conducted at the Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, Vellanikkara during the period from 1997 to 1999; to standardise the method of DNA isolation and the protocol for RAPD analysis in- black pepper so as to assess the genetic stability and clonal fidelity of tissue culture derived black pepper plants. Three methods described by Dellaporta et at. (1983); Doyle- and Doyle (1987) and Rogers and Bendich (1994) were tried. Modification of these methods were tried to find out the effect of grinding the tissue in liquid N2 and use of jJ- mercapto ethanol. The method suggested by Rogers and Bendich (1994) was found better in terms of yield and quality of DNA. Grinding with liquid N2 and use of jJ~ mercapto ethanol was found effective. Tender leaves were found to be the best source for recovery of quality DNA. Different levels and possible combinations of dNTPs, primer and enzyme were tried to standardise optimum levels of reaction components for RAPD analysis of black pepper. Best thermal cycle was identified for the amplification of black pepper genomic DNA. Different concentration of template DNA tried was found not influencing the amplification pattern. Sixty decarner primers were screened for amplification of black pepper genomic DNA. Ten primers selected for good amplification were used to screen five varieties of black pepper. Three primers, which showed polymorphism and stability of amplification, were used for analysis of TC plants. Tissue culture regenerants derived by bud culture were subjected to RAPD analysis using three primers (OPP-l, OPP-8, OPP-14). All the regenerants